Role of microbes in colorectal cancer therapy: Cross-talk between the microbiome and tumor microenvironment - Xia, Cong; Cai, Yantao; Ren, Shuangyi; Xia, Chenglai (Frontiers in Pharmacology, 2022)
The human gut microbiota is associated with the development and progression of colorectal cancer, and manipulation of the gut microbiota is a novel strategy for the prevention and treatment of colorectal cancer. Some bacteria have antitumor activity against colorectal cancer, and specific of them are able to improve the tumor microenvironment, activate immune cells and regulate cytokine secretion, thus promoting the body's immunity against tumors. In this paper, we summarize some bacteria with potential benefits in colorectal cancer and describe their roles in the tumor microenvironment, demonstrate the application of gut microbes in combination with immunosuppressive agents, and provide suggestions for further experimental studies and clinical practice applications.